Intelligent Assistance for Smart Shopping - Shraddha Gosavi; Ekta Naik; Sadhya Supalkar (International Journal of Engineering and Management Research, 2023)
Over the past few years there has been vast development in Android Application technology. This development made people's lifestyle much easier and interesting through various innovations by finding solutions to day-to-day problems. Even though many things became easier, still shopping is tough. For customers finding the required product in the supermarket is the most challenging task and moreover it is exhausting to stand in long queues at the billing counters. Shopping is a day-to-day activity. Many people visit supermarket for shopping on regular basis and during weekends, holidays and festive season supermarkets witness huge crowds. The development of online shopping websites has attracted people to purchase products online without visiting any supermarket. Mostly all the products are available on websites like Amazon, Flipkart, etc. But people cannot verify the quality of the product physically and can only verify after the product’s delivery. If the product is not up to the customer’s expectations, then it becomes a hefty task of returning and reordering the product.